BIODIESEL FROM RUBBER SEED OIL AND FOSSIL DIESEL BLENDS - FARIDI, JUNAID AHMAD (2014)
The world faces three major issues namely energy crisis, environmental pollution and food shortage. Fossil fuels are the major energy needs of the world and most of the fossil fuel resources are near to peak production and continuously depleted. To overcome this problem renewable energy sources are sought. Biodiesel is a very promising alternative liquid fuel to replace the existing fossil fuel. Biodiesel is an ecofriendly energy source due to less emission of the greenhouse gases. Currently biodiesel is mostly produced from edible oil. This may create fuel versus food controversy. Malaysia is the second largest rubber producing country in the world and rubber seed oil is underutilized and can be used for biodiesel production because it is non-edible oil. In this work, parametric optimization was done by using the response surface methodology (RSM). Parameters such as methanol to oil ratio, catalyst concentration, reaction temperature and reaction time for both acid esterification and base transesterification were studied.